APLIKASI POLLING DAN INFORMASI DENGAN SMS GATEWAY - Labib Muhajir; Muhyiddin Zainul Arifin; Tholib Hariono (KH. A. Wahab Hasbullah University, 2016)
Information and poll are important things in organization. Which with information organization can be coordinated. While poll is a democration in organitation. Application For Poll and Information is build to help those needs.Application For Poll and Information is based on literature and observations on existing polling system. Application For Poll and Information is SMS Gateway application with Visual FoxPro 9.0 programming language and Gammu. Application For Poll and Information is running on a computer to receive information through SMS and process the data into criticism, suggestions. questions and polls.Â Keywords: Poll, Information, SMS Gateway